(untitled) (Archive of Conferences, 2020)
In modern socio-economic conditions, the possibility of obtaining correspondence and evening education is very important. No less important is the task of retraining and advanced training, and here distance education is an indispensable mechanism for obtaining quality education. This is the case with the current situation (pandemiv) - the 2020 academy. Information technologies reduce the cost of distance learning and stimulate students, especially gifted children, to improve their level of knowledge in certain subjects. Distance education is important for children for whom, for some reason, we cannot provide a full-fledged education in normal school conditions.